Labour Market Institutions, Technology and Rent Sharing - Kyoji Fukao; Cristiano Perugini; Fabrizio Pompei (Institute of Labor Economics (IZA), 2020)
In this paper we analyse how labour market institutions and technology affect wage determination through rent sharing. To this aim we first extend the theoretical framework of Estevao and Tevlin (2003) to account for heterogeneity of labour (regular and non-regular workers). The predictions of the model are then tested with detailed industry-level data over four decades (1970-2012) for Japan, where the functioning of labour markets changed significantly along directions (de-unionisation, decline in standard employment and in the role of seniority) similar to the majority of advanced OECD countries. Our results indicate that such labour market evolutions weaken the capacity of regular workers to appropriate rents and might have contributed shaping the long-run wage stagnation observed in Japan. However, more advanced technologies help regular workers to appropriate higher rents.
Keywords: J30; J41; C23; 330; bargaining power; non-regular work; rent-sharing; Japan